Nocturnal Beetle Population (Coleoptera: Scarabaeidae) And Percentage Of Affected Crops In The Main Nursery Of Oil Palm (Elaeis Guineensis Jacq.) - Purnama Devi; Munzir Busniah; Zahlul Ikhsan (Jurnal Riset Perkebunan, 2022)
Rapid development of oil palm plantations in Indonesia, cause seeds requirement also increase. Nurseries are a phase that is very vulnerable to pests and diseases because the morphological sensitivity of the seedlings which are very responsive. The main pests that attack oil palm in nursery are nocturnal beetles. The objective of this study was to determine the species, population and percentage of crops attacked by the nocturnal beetles in the main nursery phase oil palm (Elaeis guineensis Jacq.). This research was conducted at the CV. Agro Unggul Sejati located in Sungai Kambut Village, Pulau Punjung District, Dharmasraya Regency. The method on this study was a survey. The sample plants were determined systematically, there were 10% of the total number of seeds in each observation block. The trapping of nocturnal beetles was carried out by light traps were installed two traps in each observation block. Observation of the percentage of affected crops was carried out by counting the sample plants that were attacked and vice versa. Two types of nocturnal beetles were found in oil palm main nursery in CV. Agro Unggul Sejati, namely Apogonia expeditionis Ritsema and Adoretus compressus Webb. Morphological characteristics of A. expeditionis are shiny black and sized 8,5-11 mm while A. compressus is reddish brown, with a body length ranging from 1-1,5 cm. The attack of nocturnal beetle cause large tears in the leaves of oil palm seedlings. The population of A. compressus was more abundant than A. expeditionis. There were 45 species of A. compressus, while 29 species of A. expeditionis. The percentage of affected crops caused by the nocturnal beetles in oil palm in the main nursery ranged from 11,12-37,03%.